(untitled) (Research, Society and Development, 2023)
The present study aims to analyze and understand the role of the father in caring for the newborn. This is an exploratory descriptive study, with a qualitative approach, developed in a public rooming-in care unit in the city of Vitória de Santo Antão - Pernambuco, in December 2022. After analyzing the data, three thematic categories emerged: role of the father in caring for the newborn child represented as protector, provider and giver of affection; Challenges of fatherhood and socioeconomic factors as obstacles to the care of newborn children by parents; Strengthening the bond, affection and companionship, as a result of the father’s participation in the care of the newborn. The study shows that fathers encounter several difficulties in caring for their newborn children, whether they be juggling work, inexperience, financial problems, among others. However, we can see a change in the father’s pattern regarding his role in caring for the mother and babies, previously considered the exclusive responsibility of the mother, a more conscious participation of the father in care in general and the expression of affections, such as love, affection and education.